Review of HEVC video encryption technology - YE Qing; LIU Xiaobing; RONG Li; HE Junfei; ZHANG Qiaojia (Tongxin xuebao)
Concerning the issue of illegal access and malicious destruction of video data during transmission and storage, a review on encryption techniques under the high efficiency video coding (HEVC) standard was conducted, starting with the HEVC standard and encryption technology. The development history of video coding technology was reviewed, and the HEVC standard was introduced. Common attack methods on video encryption technology and performance evaluation indicators were discussed. The performance, advantages, and disadvantages of different video encryption technologies were comprehensively analyzed and detailed. The development trends of video encryption technology was summarized and anticipated in order to provide reference for the research and application of video encryption technology.